A northern refugium of the Mediterranean water shrew Neomys anomalus in Słowiński National Park (N Poland) - Rychlik, Leszek; Stachowiak, Agnieszka; Nowak, Urszula; Kardynia, Paweł (Biological Letters, 2013)
The influence of recent anthropogenic and climatic changes on the distribution or population size of individual species should be especially pronounced at the boundaries of their geographical ranges. Therefore, in summers 2008-2010, we live-trapped small mammals and analysed habitat features on 14 study plots comprising various wet habitats of Słowiński National Park (at the Baltic coast in northern Poland) in order to recognize the current distribution and population size of Neomys anomalus Cabrera, 1907 in its northernmost population in Europe. N. anomalus was, however, captured only on one plot - a wet, unmown meadow crossed by unkempt drainage ditches, situated on the Gać Peninsula (Półwysep Gacki). This result, compared to historical data, suggests that neither the abundance of N. anomalus has increased nor its range has been extended. We give a detailed description of the habitat in this study plot. The information can be useful in the protection of this rare shrew species with very specific habitat requirements.